2018
DOI: 10.1111/dom.13322
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of MYL‐1501D vs insulin glargine in patients with type 1 diabetes after 52 weeks: Results of the INSTRIDE 1 phase III study

Abstract: The upper 95% CI limit for mean change in HbA1c at week 24 indicated that MYL-1501D was non-inferior to reference insulin glargine. There were no clinically meaningful differences between groups in incidence of overall and nocturnal hypoglycaemia, local or systemic reactions, safety or immunogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 25 publications
4
47
0
1
Order By: Relevance
“…Changes from baseline in terms of the incidence of TEAR were similar between the treatment‐switching and reference insulin glargine treatment sequences. These results suggest that both insulin glargine preparations demonstrated similar immunogenic potential, and switching patients from MYL‐1501D to reference insulin glargine and back to MYL‐1501D did not impact immunogenicity; these results further confirm the similar safety profiles of MYL‐1501D and reference insulin glargine demonstrated in earlier studies . The TEAR findings of the present study were similar to the immunogenicity and safety results of a study comparing another insulin glargine biosimilar (LY2963016) and reference insulin glargine in which the proportion of participants with detectable TEAR was similar between treatment groups, providing additional evidence to support the development and use of biosimilars or FOBs for therapeutics such as insulin …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Changes from baseline in terms of the incidence of TEAR were similar between the treatment‐switching and reference insulin glargine treatment sequences. These results suggest that both insulin glargine preparations demonstrated similar immunogenic potential, and switching patients from MYL‐1501D to reference insulin glargine and back to MYL‐1501D did not impact immunogenicity; these results further confirm the similar safety profiles of MYL‐1501D and reference insulin glargine demonstrated in earlier studies . The TEAR findings of the present study were similar to the immunogenicity and safety results of a study comparing another insulin glargine biosimilar (LY2963016) and reference insulin glargine in which the proportion of participants with detectable TEAR was similar between treatment groups, providing additional evidence to support the development and use of biosimilars or FOBs for therapeutics such as insulin …”
Section: Discussionsupporting
confidence: 89%
“…Although there were numerically more nocturnal hypoglycaemic events in the MYL‐1501D treatment sequence compared with the reference insulin glargine treatment sequence, this trend was probably not related to treatment because the trend was consistent across all three treatment periods, including when participants were receiving reference insulin glargine. Overall, the safety results support the safety results of INSTRIDE 1 and INSTRIDE 2 and indicate that the two sequence groups in the present study had equivalent safety profiles throughout the study at the end of the treatment period, and switching treatments had no impact on TEAEs, hypoglycaemic events, immunogenicity profiles, or other safety variables.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Among 405 candidate studies identified from electronic databases and other sources, 10 randomized trials (4935 patients) were assessed, including 8 studies on long-acting biosimilar insulins [11][12][13][14][15][16][17][18] (2 each on LY2963016, MK-1293 and Mylan's insulin glargine, and 1 each on FFP-112 and Basalog: 3923 patients) and 2 studies on short-acting biosimilar insulin 19,20 (both on SAR342434 insulin lispro: 1012 patients; Appendix S4).…”
Section: Resultsmentioning
confidence: 99%